2019
DOI: 10.1111/ele.13242
|View full text |Cite
|
Sign up to set email alerts
|

A balance of winners and losers in the Anthropocene

Abstract: Scientists disagree about the nature of biodiversity change. While there is evidence for widespread declines from population surveys, assemblage surveys reveal a mix of declines and increases. These conflicting conclusions may be caused by the use of different metrics: assemblage metrics may average out drastic changes in individual populations. Alternatively, differences may arise from data sources: populations monitored individually, versus whole‐assemblage monitoring. To test these hypotheses, we estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
227
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 227 publications
(249 citation statements)
references
References 48 publications
(75 reference statements)
21
227
1
Order By: Relevance
“…These temporal analyses are particularly attractive now because of the outstanding technical advances occurred during the last decade, in which prior work has developed approaches to separate causality from correlation (Sugihara et al, 2012), to obtain information of species interactions from noisy and nonlinear time-series data (Cenci, Sugihara, & Saavedra, 2019) and to relate such information to a structural stability approach (Cenci et al, 2019). The only step remaining step is to analyse databases containing the introduction of exotic species along time, and fortunately, this particular information has been published very recently (Dornelas et al, 2019).…”
Section: Estimation Of Species Interactions From Variation In Speciesmentioning
confidence: 99%
“…These temporal analyses are particularly attractive now because of the outstanding technical advances occurred during the last decade, in which prior work has developed approaches to separate causality from correlation (Sugihara et al, 2012), to obtain information of species interactions from noisy and nonlinear time-series data (Cenci, Sugihara, & Saavedra, 2019) and to relate such information to a structural stability approach (Cenci et al, 2019). The only step remaining step is to analyse databases containing the introduction of exotic species along time, and fortunately, this particular information has been published very recently (Dornelas et al, 2019).…”
Section: Estimation Of Species Interactions From Variation In Speciesmentioning
confidence: 99%
“…Change in the numbers of species through time at scales smaller than the globe (i.e. in the absence of speciation) will depend on the balance between losses and gains of species from one point in time to the next (Sax et al 2002, Jackson and Sax 2010, Batt et al 2017, Dornelas et al 2019. In this article, we do not enter into the debate about whether fine-scale species richness is changing in the face of human activities (Vellend et al 2013, 2017a, Dornelas et al 2014, Gonzalez et al 2016, Cardinale et al 2018, but rather simply acknowledge that the observed pattern of change is variable, with some intriguing biogeographic and taxonomic variation (Newbold et al 2015, Blowes et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Together, non-native and synanthropic species contribute to biotic homogenization across space and time (McKinney, 2006). Those populations that have increased in abundance during the Anthropocene are as species rich as those that have declined (Dornelas et al, 2019), a pattern that can lead to stable local species richness despite striking changes in community composition (Dornelas et al, 2014;Magurran et al, 2018). Combined with the recognition that a major facet of biodiversity loss is the declining population size of many native species (Ceballos, Ehrlich, & Dirzo, 2017;Hallmann et al, 2017;Young, McCauley, Galetti, & Dirzo, 2016), this has led to an increasing focus on monitoring patterns of organisms' abundance over space and time (Hillebrand et al, 2018).…”
Section: Introductionmentioning
confidence: 99%